Ethical considerations for committees, supervisors and student researchers conducting qualitative research with young people in the United Kingdom. (December 2021) - Lenton, Lindsay A.; Smith, Victoria; Bacon, Alison M.; May, Jon; Charlesford, Jaysan
Abstract: When investigating issues surrounding young people it is necessary to involve them in the discussion of the topic. It is also necessary that the inexperienced or student researcher is equipped with the skills needed to navigate ethical quandaries that may arise. This article considers some of the ethical issues that can arise for novice researchers in institutions that do not have a firmly established qualitative research tradition, with particular reference to research with young people and in some instances sensitive topics. Examples of how the embedding of particular research practices into an ethical framework can navigate these quandaries are made. These include Training & Skills, Recruitment & consent, Breaking the ice, disclosures and endings. Recommendations for updates to ethical procedures for qualitative psychological research are made.